DEVELOPMENT OF THAI LITERATURE READING LITERACY AND CREATIVE THINGKING OF GRADE 9 STUDENTS THROUGH CREATIVITY-BASED LEARNING COMBINED WITH CREATIVE ART ACTIVITIES - Jampamuang , Ekkarat; Doungwilai, Dhanita (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2024)
This research aimed: 1) to develop the ability to read Thai literature of grade 9 students by organizing creative-based learning combined with creative art activities, with the goal of having 80 percent of students passing the criteria of 80 percent or higher, and 2) to develop the creative thinking abilities of grade 9 students by using creative learning management alongside creative art, aiming for 80 percent of students to meet the criteria with 80 percent or more. The target group was Mathayom 3/4 students at Kham Kaen Nakhon School, located in Sila Subdistrict, Mueang District, Khon Kaen Province. This research was an action research. The tools used in the research included lesson plans, learning management results recording forms, student learning behavior observation forms, creative thinking ability assessment forms, tests to measure knowledge ability in reading Thai literature at the end of the operational cycle, assessments of knowledge ability in reading Thai literature, and tests to measure creative thinking ability at the end of the practice cycle. Statistics used in data analysis were divided into 2 types: 1) Analyzing quantitative data by finding the mean standard deviation (SD) and percentage %, and 2) Analyzing qualitative data. Data were analyzed using descriptive content analysis. The research results were as follows: 1) students had 82.43 % ability in reading literacy Thai literature, and students who passed the criteria account for 83.87 % or more, which was higher than the specified criteria, and 2) students had creative thinking ability of 90.32 % and students who passed the criteria were 84.62 % or more, which was higher than the specified criteria.